The Question of Esoteric Writing in Machiavelli’s Works - Namazi, Rasoul (Renaissance and Reformation / Renaissance et Réforme, 2017)
The question addressed by this article is whether esotericism or secret teachings exist in Machiavelli’s writings. This question has been a major point of contention between the commentators of Machiavelli, with many denying the existence of esoteric teaching in the Machiavellian corpus. This article will explore the controversy by studying Machiavelli’s own works, and on this basis it will be contended that there are many references and elements present in Machiavelli’s works that justify an esoteric interpretation. Consequently, it is reasonable to assume that Machiavelli has esoteric intentions that are different from the surface meaning of his texts. It is therefore necessary for commentators to go beyond the surface of his writings to uncover his deeper teachings.